Characterization of human adrenal cytochrome P450 11B2 products of progesterone and androstenedione oxidation - Glass, Sarah M. (J Steroid Biochem Mol Biol, 2020)
Cytochrome P450 (P450) 11B1 and 11B2 both catalyze the 11β-hydroxylation of 11-deoxycorticosterone and the subsequent 18-hydroxylation of the product. P450 11B2, but not P450 11B1, catalyzes a further C-18 oxidation to yield aldosterone. 11-Oxygenated androgens are of interest, and 11-hydroxy progesterone has been reported to be a precursor of these. Oxidation of progesterone by purified recombinant P450 11B2 yielded a mono-hydroxy derivative as the major product, and co-chromatography with commercial standards and 2-D NMR spectroscopy indicated 11β-hydroxylation. 18Hydroxyprogesterone and a dihydroxyprogesterone were also formed. Similarly, oxidation of androstenedione by P450 11B2 yielded 11β-hydroxyandrostenedione, 18-hydroxyandrostenedione, and a dihydroxyandrostenedione. The steady-state kinetic parameters for androstenedione and progesterone 11β-hydroxylation were similar to those reported for the classic substrate 11-deoxycorticosterone. The source of 11α-hydroxyprogesterone in humans remains unresolved.